The virtues of native discourse: Striking a balance between English and the native language - Eva Forslund; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2022)
An increasing number of researchers, whether in Sweden, Slovakia, Italy, Japan, Brazil, or many other places, are using English in their discourse, written or oral, despite working in a place where the native language is not English. To convey insights and research results to the general public or to domestic policymakers, one must write in the native language. Language affects the way students learn and the content of teaching. Working in a second language can adversely affect learning unless teachers compensate for certain effects. When English is the working language, there is a risk that the study of relevant national, regional, and local institutions and conditions will be downplayed, which may impair students' understanding of the workings of the country where most of them will pursue their future careers. Also, there is a risk that important domestic aspects will be overlooked as researchers seek to treat topics sufficiently general to appeal to 'international journals,' which use English. The authors are Swedes and economists, and here often use illustrations from economics in Sweden, but the issue arises widely and increasingly, in many areas of learning and throughout the world.
Keywords: A1; A2; B4; 330; Economic policy; Economics teaching; Economics writing; Institutions; Language of instruction